The commercialisation of Trichogrammatoidea cryptophlebiae (Nagaraja) in South Africa - Stirk, Emma Jane (Rhodes University, 2026)
Trichogrammatoidea cryptophlebiae (Nagaraja) is an endemic egg parasitoid from southern Africa that shows great potential as a biological control agent for tortricid pests in high-value export crops. This study aimed to develop an integrated framework for its use in pest management by addressing three critical aspects: optimising mass-rearing protocols in the laboratory, evaluating parasitism efficacy in the field across different crops and release strategies, and assessing non-target effects from agrochemical residues. In the laboratory, a series of controlled trials were conducted to identify key indicators of parasitoid quality, including parasitism rate, emergence success, sex ratio, and morphological traits such as hind tibia length and body length. Host egg age, female age, and foundress-to-host ratios significantly influenced reproductive output and fitness. These results were used to refine rearing methods to maximise the production of high-quality, fecund females suitable for release. Field trials in macadamia, grape, litchi, and pome fruit orchards revealed that the timing and intensity of parasitoid releases had a significant impact on parasitism rates. Both standard and late season releases consistently produced the highest levels of parasitism, likely due to better synchronisation with host egg availability and fewer environmental constraints. Increased release numbers also resulted in improved parasitism, indicating a positive density-dependent effect under natural conditions. To ensure that field releases are compatible with existing pest control practices, a comprehensive assessment of chemical residues on adult and pre-imaginal life stages was conducted. It was found that several commonly used insecticides and fungicides had significant sublethal effects, reducing emergence, skewing sex ratios, and impairing reproductive potential, even when direct mortality among adults was low. These findings were assigned toxicity classifications determined by the International Organisations for Biological Control (IOBC), providing practical guidance on chemical compatibility for growers. This research offers practical recommendations for the successful implementation of T. cryptophlebiae in integrated pest management systems. These recommendations include optimised rearing and quality control protocols, evidence-based release strategies tailored to pest phenology, and informed selection of agrochemicals to ensure parasitoid survival and efficacy. Together, these contributions enhance the viability of biological control in export-driven agriculture, promoting more sustainable and environmentally responsible pest management in South Africa.
from mass-rearing to augmented field releases
Keywords: Biological pest control agents (http://id.loc.gov/authorities/subjects/sh89006480); Tortricidae -- Biological control (http://id.loc.gov/authorities/subjects/sh2010002243); Introduced organisms (http://id.loc.gov/authorities/subjects/sh2002000268); Entomology; Trichogrammatoidea cryptophlebiae (https://www.wikidata.org/wiki/Q14070313); Egg parasitoid (https://www.wikidata.org/wiki/Q111109486)